DETERMINAN PEMILIHAN KARIR SEBAGAI AKUNTAN PUBLIK OLEH MAHASISWA AKUNTANSI - Tri Kusno Widi Asmoro; Anita Wijayanti; Suhendro Suhendro (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2015)
Abstract The purpose of this research is to analyze some factors which can influence the accounting students’ interest at Batik Islamic University and the Sebelas Maret University Surakarta. This research sample using purposive sampling. The samples are 100 respondents. The analytical method is multiple linear regression.The results of this research shown that partially only factor training of professionals who have a significant influence on career selection of students S1 accounting to be public accounting. Meanwhile the salary factor, professional recognition, work environment, social values, consideration of the labor market, and personality have no significant effect. Whereas, simultaneously concluded that the factors of salaries, professional training, professional recognition, work environment, social values, labor market considerations, and personality have a positive and significant influence on student career selection of S1 accounting to be public accounting. Keywords: Career, students, public accounting.